EFEKTIVITAS BUKU AJAR INTERAKTIF PAI DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF, MOTIVASI BELAJAR, DAN INTERNALISASI NILAI-NILAI KEAGAMAAN PESERTA DIDIK - Desiana; Sulthan Syahrir, Meriyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of interactive Islamic Religious Education (PAI) textbooks in improving cognitive learning outcomes, learning motivation, and internalization of religious values of students in Elementary Schools in Bandar Lampung City. Using the Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, this study focuses on the development of innovative and research-relevant teaching materials. This study will focus on the development of interactive PAI textbooks for grade IV elementary school students. The results of the study indicate that the use of interactive textbooks significantly improves students' cognitive learning outcomes through the presentation of more interesting, visual, and easy-to-understand materials. In addition, interactive elements in the teaching materials have proven to be very effective in generating and maintaining students' learning motivation, creating a learning environment that is not monotonous and more participatory. Furthermore, this textbook facilitates the internalization of religious values by instilling Islamic teachings and values in depth, contextually, and applicatively. Thus, the development and implementation of interactive PAI textbooks using the R&D approach and the ADDIE model is an effective strategy to optimize the learning process and achieve comprehensive PAI education goals.